'Walking along with development': Climate resilient pathways for political resource curses. Issue 128 (February 2022) - Butler, J.R.A.; Wise, R.M.; Meharg, S.; Peterson, N.; Bohensky, E.L.; Lipsett-Moore, G.; Skewes, T.D.; Hayes, D.; Fischer, M.; Dunstan, P.
Abstract: Adaptation pathways are decision-making processes which sequence actions over time to account for rapid change and future uncertainty. In developing economies pathways practice can guide climate-resilient development (CRD) but is hampered by complex political dynamics, intensified by 'resource curses' of abundant natural resources. We tested an adaptation pathways approach for large-scale natural resource development in Papua New Guinea's Bismarck Sea. We engaged with five contested development proposals for deep sea mining, oil palm and tourism to integrate CRD principles into decision-making. The process involved three steps: mapping decision-making and power, participatory pathways planning, and evaluation and learning. CRD-relevant information was fed into decision-making about the proposals. 'Political spaces' were created through participatory planning that levelled power asymmetries, enabled common interests to emerge, democratised knowledge co-production, enhanced networks and coordination, and galvanised collective action to re-design the proposals with CRD considerations. The common political interests formed leverage points for conflict transformation and collaboration. Evaluation revealed the suspension of an oil palm development to allow a landuse plan to be formulated to account for food security, conservation and climate adaptation. The study highlighted three learnings: the importance of analysing politics and power in decision-making and identifying leverage points; the challenges for researchers wishing to create political spaces; and the necessity for capacity-building amongst local knowledge brokers to continue this role. We conclude by assessing the feasibility of mainstreaming this approach into decision-making in resource curses, dubbed by one decision-maker as 'walking along with development'. Highlights: Large-scale development decisions are highly political and potentially maladaptive. We test an adaptation pathways approach to mainstream climate change into decisions. Analysing power enabled the creation of political spaces for conflict transformation. Leverage points of mutual political interest allowed redesign of development proposals. Capacity of local knowledge brokers must be supported to maintain pathways processes.